Singlet Fission, Polaron Generation and Intersystem Crossing in Hexaphenyl Film - Wenjun Ni; Tianjiao Li; Christian Kloc; Licheng Sun; Gagik G. Gurzadyan (Molecules, 2022)
The ultrafast dynamics of triplet excitons and polarons in hexaphenyl film was investigated by time-resolved fluorescence and femtosecond transient absorption techniques under various excitation photon energies. Two distinct pathways of triplet formation were clearly observed. Long-lived triplet states are populated within 4.5 ps via singlet fission-intersystem crossing, while the short-lived triplet states (1.5 ns) are generated via singlet fission from vibrational electronic states. In the meantime, polarons were formed from hot excitons on a timescale of <30 fs and recombined in ultrafast lifetime (0.37 ps). In addition, the characterization of hexaphenyl film suggests the morphologies of crystal and aggregate to wide applications in organic electronic devices. The present study provides a universally applicable film fabrication in hexaphenyl system towards future singlet fission-based solar cells.